2009
DOI: 10.1158/1078-0432.ccr-08-2166
|View full text |Cite
|
Sign up to set email alerts
|

AKT/mTOR Pathway Activation and BCL-2 Family Proteins Modulate the Sensitivity of Human Small Cell Lung Cancer Cells to RAD001

Abstract: Purpose:The Akt/mammalian target of rapamycin (mTOR) pathway is frequently activated in human cancers and plays an important role in small cell lung cancer (SCLC) biology.We investigated the potential of targeting mTOR signaling as a novel antitumor approach in SCLC. Experimental Design:The expression of mTOR in patient specimens and in a panel of SCLC cell lines was analyzed. The effects on SCLC cell survival and downstream signaling were determined following mTOR inhibition by the rapamycin derivative RAD001… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 44 publications
1
68
1
Order By: Relevance
“…The observation that Bcl-2 expression was elevated in primary SCLC, in comparison with normal lung tissue further supports this model, in view of the overexpression of p110-a. Importantly, the Bcl-2 family of proteins has been previously shown to play a crucial role in the survival of SCLC cell lines in vitro and in vivo (5,(22)(23)(24)(25)(26). The p110-a inhibitors induced increases in both SCLC apoptosis and autophagy, which is consistent with Bcl-2 family proteins being a target of p110-a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that Bcl-2 expression was elevated in primary SCLC, in comparison with normal lung tissue further supports this model, in view of the overexpression of p110-a. Importantly, the Bcl-2 family of proteins has been previously shown to play a crucial role in the survival of SCLC cell lines in vitro and in vivo (5,(22)(23)(24)(25)(26). The p110-a inhibitors induced increases in both SCLC apoptosis and autophagy, which is consistent with Bcl-2 family proteins being a target of p110-a.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously evaluated the mTOR inhibitor everolimus in SCLC cell lines and found that it was effective in a subset of SCLC cell lines characterized by activation of the Akt/mTOR pathway and low expression levels of antiapoptotic Bcl-2 family proteins (24). In view of the results obtained with isoform-selective inhibitors of p110-a, it can be speculated that these agents may be more potent, as they induce a downregulation of antiapoptotic Bcl-2 family proteins and of the activity of the Akt/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is an important target in the treatment of hematopoietic system tumors (Kawauchi et al, 2009). Marinov et al (2009) found in their studies an increase of mTOR activtiy in small cell lung cancer cell lines and in vivo. The rapamycin derivative, RAD001, can be used to inhibit mTOR activity and increase etoposide cytotoxicity in small cell lung cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Although in this manuscript we have focused in the study of genes involved in angiogenesis and migration, the regulation of other genes nicely correlates with the phenotype of the NSCLC cell line H460cri when compared with H460v cells. Among these genes are: phosphoinositide-3-kinase regulatory subunit 1-a (PIK3R1) (À4.26 fold), which is a regulator of AKT/ PKB signaling pathway, is involved in cell survival and has been implicated in poor responses to chemotherapy in lung cancer (Downward, 2008;Marinov et al, 2009;Sos et al, 2009); dickkopf homolog-1 (DKK1) (À3.36 fold) , a potent antagonist of Wnt signaling, is expressed at high levels in lung and esophageal carcinomas (Yamabuki et al, 2007) and hepathocarcinomas (Yu et al, 2009); tissue-type plasminogen activator (PLAT) (À4.949 fold) has been previously found significantly downregulated in nonangiogenic NSCLC tumors as compared with angiogenic tumors (Offersen et al, 2007), and therefore its downregulation in H460cri cells agrees with its reduced angiogenic potential; epidermal growth factor receptor (EGFR) (À3.29 fold) has been intensely studied, not only to understand the mechanisms underlying its oncogenic potential, but also to exploit as a therapeutic target (Hynes and MacDonald, 2009) as inhibition of its activity decreases lung cancer cell growth in tumors, which show mutated versions of this receptor. Finally, BMP2 has been found overexpressed in human NSCLC, with little or no expression in normal lung tissue or benign lung tumors, (Langenfeld et al, 2003) suggesting that BMP2 may enhance tumor progression.…”
Section: Dusp1 Participates In Tumor Progression In Nsclcmentioning
confidence: 99%